The influence of ultrasonic radiation of low intensity in cultured fibroblast cells - Bertin, Larissa Dragonetti; Pires-Oliveira, Deise Aparecida Almeida; Oliveira, Priscila Daniela; Serpeloni, Juliana Almeida; Szezerbaty, Stheace Kelly Fernandes; Santos, João Paulo Manfre; Oliveira, Rodrigo Franco (Manual Therapy, Posturology & Rehabilitation Journal, 2015)
Introduction: In vitro and in vivo put in evidence that the Low Intensity Pulsed Ultrasound therapy exerts a significant influence on cell function (cytoskeleton organization, stimulation of mitochondrial activity, ATP levels and plasma membrane). Objective: This study will analyze the radiation of low intensity pulsed ultrasound in fibroblast cells L 929. Method: In this study are presented the data from each exposure group average and standard deviation in each moment of evaluation (24 hours, 48 hours and 72 hours). The control group (received no radiation), 0.2 W/cm2 with 10% pulse regime (1: 9 duty cycle), 0.2 W / cm2 with 20% pulse regime (2: 8 cycle work), 0.4 W/cm2 with pulse scheme 10% (1: 9 duty cycle), 0.4 W/cm2 with pulse scheme 20% (2: 8 duty cycle). The analyzes will be performed through optical microscopy, MTT method 3 - (4,5-dimethylthiazol-2-yl) -2,5 diphenyl tetrazolium bromide, within the incubation times of 24, 48 and 72 hours. Results: Given the above study, the results presented in this project will be directed to increase the stimulation process and proliferation of fibroblast cells from the pulsed ultrasonic irradiation of low intensity, correlating with the healing process, neovascularization and repair. Conclusion: Therefore, the study of the effect of ultrasound from cell culture provides us with a simple and informative model on the significant aspects of the use of physical therapy in vivo system.